Early Life and Postnatal Western Diet Feeding and Susceptibility to Chemically Induced Colonic Aberrant Crypt Foci in Male Rats Offspring - Lopes, Gisele Aparecida Dionísio [UNESP]; Dias, Marcos Correa [UNESP]; Barbisan, Luís Fernando [UNESP]; Marchesan Rodrigues, Maria Aparecida [UNESP] (Taylor & Francis, 2016)
The modifying effects of a Western diet (WD) during early life on the susceptibility to colon carcinogenesis induced by dimethylhydrazine (DMH) were examined in male rats as later adults. Three groups were studied: a lifetime control diet-fed group, a test group fed WD since pregnancy from dams until postnatal day (PND) 42, and a group fed WD at adulthood. At PND 70, all groups received the carcinogen DMH and were euthanized 10 wk later. Colonic aberrant crypt foci (ACF) were scored (number and crypt multiplicity) and the altered pattern of β-catenin expression was evaluated in the colonic lesions. ACF multiplicity (≥4 crypts) was significantly higher in the group fed WD at early life than in the group fed the control diet. ACF number, crypt multiplicity, and the number of high-grade dysplastic lesions were significantly higher in the group fed WD at adulthood than in the groupfed the control diet. The number of lesions with altered β-catenin expression was higher in the groups receiving WD at early life or at adulthood than in the lifetime control-diet-fed group. These findings indicate that WD exposure at early life increased the susceptibility to colon carcinogenesis at adulthood.